Answer:
y = -2x^2 -4x +1
Step-by-step explanation:
y-3 = -2 (x+1)^2
Foil (x+1)^2
(x+1)(x+1) = x^2 +x+x+1 = x^2 +2x+1
Substitute this back in
y-3 = -2(x^2 +2x+1)
Distribute
y-3 = -2x^2 -4x -2
Add 3 to each side
y-3+3 = -2x^2 -4x -2+3
y = -2x^2 -4x +1
Answer:
cxc joy
Step-by-step explanation:
jouning
Answer:
A) 120
Step-by-step explanation:
For this question you will need to use factorials
5! =5×4×3×2×1
which equals to 120
therefore the 5 people can be selected in 120 different ways
hope this helps